ALOPECIA AREATA IS NOT ASSOCIATED WITH HELICOBACTER PYLORI - Abdel Hafez, Hisham Zayan (Medknow Publications, 2009)
BACKGROUND: Alopecia areata (AA) is an immune-mediated form of hair loss that occurs in all ethnic groups, ages, and both sexes. Helicobacter pylori has been associated with many extra-digestive dermatological conditions. The causal relation between alopecia areata and Helicobacter pylori is discussed in this study. MATERIALS AND METHODS: We have screened for the presence of H. pylori in patients with AA, in order to determine any potential role in its patho-physiology. We have prospectively studied 31 patients with alopecia areata and 24 healthy volunteers of similar gender, for the presence of H. pylori stool antigen (HpSAg). RESULTS: Optical density values for H. pylori infection was positive in 18 of the 31 patients evaluated (58.1%), while in 13 patients, the values did not support H. pylori infection (41.9%). In the control group, 10 of the 24 (41.7%) had positive results. Within the group of alopecia areata, there was no significant difference between HpSAg positive and negative patients. CONCLUSIONS: The results have shown that a relation between Helicobacter pylori and alopecia areata is not supported. We advise that H. pylori detection need not to be included in the laboratory work up of alopecia areata.